The art of critical thinking logic for Filipino students - Buenaflor, Lionel E. (Books Atbp. Publishing Corp., 2019)
"The book teaches the students the proper method of making critical analysis for the purpose of obtaining the truth. This new edition is focused on a more detailed approach to the understanding of logic. It highlights the logic of arguments to provide the students a better training on reasoning. This book intends to help the students develop a more fruitful reasoning process by making them understand the importance of using logical reasoning in their everyday life. In this regard, classroom exercises and activities are improved in this edition for the purpose of better understanding the critical thinking processes and, eventually, for a better result. "--Preface.